In Vitro Characterization of the Pyrazole-Carrying Synthetic Cannabinoid Receptor Agonist 5F-3,5-AB-PFUPPYCA and its Structural Analogs - M.H. Deventer; C. Norman; R. Reid; C. McKenzie; N.N. Daeid; C.P. Stove (Emerging Trends in Drugs, Addictions, and Health)
Introduction: Pyrazole-carrying “FUPPYCA” synthetic cannabinoid receptor agonists (SCRAs) have made short-lived appearances on the market since 2015. However, 5F-3,5-AB-PFUPPYCA and 3,5-ADB-4en-PFUPPYCA have recently been detected in Scottish prisons. This re-emergence is believed to be triggered by the Chinese generic SCRA ban (2021). Methods: Infused paper samples, seized from different Scottish prisons were analyzed to assess the prevalence of FUPPYCA SCRAs. Six structurally related analogs were then functionally characterized using live cell receptor-based assays, based on the functional complementation of a nanoluciferase enzyme. Results: 5F-3,5-AB-PFUPPYCA and 3,5-ADB-4en-PFUPPYCA mixtures were detected 9 times in Scottish prisons since July 2021. Most FUPPYCA SCRAs were found to be inactive at both CB1 and CB2, with only 3 analogs showing some (minor) CB1 activation potential (3,5-AB-CHMFUPPYCA, 5,3-AB-CHMFUPPYCA and 5,3-ADB-4en-PFUPPYCA). Interestingly, the 5,3 regioisomers (covered by the ban) were more active than their 3,5 counterparts. Furthermore, all analogs had antagonistic properties, potentially related to their structural resemblance to cannabinoid antagonists. Conclusions: Given their weak CB activity, FUPPYCA SCRAs are not expected to pose a serious health hazard, despite their ability to evade the generic ban. This may also explain their only transient re-emergence in Scottish prisons.